2016
DOI: 10.1007/s00506-016-0308-5
|View full text |Cite
|
Sign up to set email alerts
|

Grundlegende Prozesse betreffend Hydraulik, Sedimenttransport und Flussmorphologie an der Donau

Abstract: Zusammenfassung Im Rahmen des Pilotprojektes Bad Deutsch-Altenburg wurde vor, während und nach der gleichzeitigen Umsetzung mehrerer Maßnahmen (Buhnenumbau, Granulometrische Sohlverbesserung – GSV, Uferrückbau und Gewässervernetzung) ein umfassendes Monitoringprogramm durchgeführt. Ziel war es, neben der Ist-Zustandserfassung, Begleitung und Dokumentation der Bauphase und der Erfassung der Entwicklung nach Bau auch die zugrunde liegenden Prozesse hinsichtlich Hydraulik, Sedimenttransport und Flussmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Besides issues of handling the devices (installation, operation and service), concerns about the validity and explanatory power of time-averaged bed shear stresses were raised. Gmeiner et al [84] and Liedermann et al [85] showed that bed load transport takes place below expected discharges considering the concepts of Shields [86] and Zanke [87] for critical shear stresses. It is thus recommended to consider time series of bed shear stresses including fluctuations for which probabilistic approaches [88][89][90][91] are suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Besides issues of handling the devices (installation, operation and service), concerns about the validity and explanatory power of time-averaged bed shear stresses were raised. Gmeiner et al [84] and Liedermann et al [85] showed that bed load transport takes place below expected discharges considering the concepts of Shields [86] and Zanke [87] for critical shear stresses. It is thus recommended to consider time series of bed shear stresses including fluctuations for which probabilistic approaches [88][89][90][91] are suitable.…”
Section: Discussionmentioning
confidence: 99%